2022
DOI: 10.3389/fgene.2022.848557
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulations of Perineural Invasion in Head and Neck Squamous Cell Carcinoma

Abstract: Carcinomas of the oral cavity and oropharynx belong among the ten most common malignancies in the human population. The prognosis of head and neck squamous cell carcinoma (HNSCC) is determined by the degree of invasiveness of the primary tumor and by the extent of metastatic spread into regional and distant lymph nodes. Moreover, the level of the perineural invasion itself associates with tumor localization, invasion’s extent, and the presence of nodal metastases. Here, we summarize the current knowledge about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 229 publications
0
3
0
Order By: Relevance
“…Several other studies demonstrated an association between the epigenetic regulation of specific candidate genes by altered DNA methylation and the development of PNI [42][43][44][45][46][47][48][49][50]. Still, the DNA methylation status in head and neck squamous cell carcinoma has not yet been studied sufficiently [50]. Consistent with these studies, genome-wide DNA hypomethylation was evident in ML A HNSCC at least in part due to truncating NSD1 mutations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Several other studies demonstrated an association between the epigenetic regulation of specific candidate genes by altered DNA methylation and the development of PNI [42][43][44][45][46][47][48][49][50]. Still, the DNA methylation status in head and neck squamous cell carcinoma has not yet been studied sufficiently [50]. Consistent with these studies, genome-wide DNA hypomethylation was evident in ML A HNSCC at least in part due to truncating NSD1 mutations.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the DNA methylation of the CDKN2A promoter was a more frequent event in aggressive prostatic tumors with PNI [41]. Several other studies demonstrated an association between the epigenetic regulation of specific candidate genes by altered DNA methylation and the development of PNI [42][43][44][45][46][47][48][49][50]. Still, the DNA methylation status in head and neck squamous cell carcinoma has not yet been studied sufficiently [50].…”
Section: Discussionmentioning
confidence: 98%
“…Especially, the hallmarks epithelial mesenchymal transition pathway overlapped with the DNA mutation mentioned above, TGFBR1 . EMT is a process by which polar epithelial cells are transformed into mesenchymal cells with a significantly enhanced ability to migrate and invade the surrounding tissues and already well known for its relationship with PNI in HNSCC 7 , 16 . There were strong expression of BDNF, TrkB, and p75NGFR in perineural tumor cells of human cutaneous squamous cell carcinoma 17 , and over-expression of TrkB results in altered expression of molecular mediators of EMT, including downregulation of E-cadherin and upregulation of Twist in HNSCC 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the complex anatomical structure and concealability of the disease as well as the high demand for functional preservation make the choice of surgical approach more challenging, resulting in a low surgical cure rate and poor postoperative prognosis, with approximately 60% survival at 5 years [ 2 , 5 ]. Lymphatic metastasis (LM) and degree of primary tumor invasion are the main factors affecting the prognosis of HNSCC [ 6 ]. In previous studies, LM has been shown to be an independent prognostic factor for HNSCC [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%